Determinants of adverse childhood experiences and substance use among emerging adults in the context of sustainable development goals - Ajith K. Remesan; Varalakshmi Chandra Sekaran; Teddy Andrews Jaihind Jothikaran; Kalpana Goel; Lena Ashok (PLoS ONE, 2025)
Introduction Adverse childhood experiences (ACEs) are linked to an increased risk of developing substance use among emerging adults, which adversely affects achieving the Sustainable Development Goals (SDGs). This study explored various sociocultural and socio-economic factors associated with emerging adults as predictors of ACEs and substance use. Methods Data was collected from 957 emerging adults studying bachelor’s degrees in 12 colleges at Mangalore University in the Udupi district, Karnataka, India. The tools for data collection included sociodemographic pro forma, Alcohol Smoking and Substance Involvement Screening tool developed by the World Health Organization (WHO ASSIST version 3.0) to assess substance use, and the Adverse Childhood Experiences Scale to determine the adverse experiences in childhood. Results The study found that the prevalence of substance use was 17.97%, while the prevalence of Adverse Childhood Experiences (ACEs) was 18.91% in the sample examined (172 and 181 participants among the total sample of 957, respectively). The mean age for substance use initiation was 17.26 years. ACEs operated as a risk element for emerging adults’ substance use, whereas living with parents protected against it. In addition, the parents who lived together and served as primary caregivers could protect against ACEs. Family and peer group substance use was found to be associated with an increased likelihood of ACEs. Conclusion Various sociocultural and socioeconomic factors predicted substance use and ACEs. The significance of family was revealed in the study since families without substance use and parental supervision served as a defense against both substance use and ACEs.